IMPLEMENTASI QUALITY OF SERVICE MENGGUNAKAN METODE QUEUE TREE DAN MANGLE PADA MIKROTIK ROUTER OS DI PT BATAM BINTAN TELEKOMUNIKASI - Sianturi, Apoan Toni Corline; Pastima Simanjuntak (Computer Science and Industrial Engineering, 2024)
With the rapid development technology network, management of a management network system be appropriate and correct. The number of users in accessing a network causes the network to be busy so that it will disrupt the smooth system of a network. Settings in managing network quality make data network access better and more optimal and support the smooth process of data transfer when accessing the internet. However, as the number of customers and partners increases, there must be additional value applied by the company. Constraints that will be found when a provider does not implement a network quality management system properly will cause an imbalance in the user's capacity to use internet services from the provider, thereby disrupting traffic stability and causing congestion on the internet network flow so that the bandwidth quality mechanism will be disrupted when accessing the network in real time. This also causes the network of uplinks that are delivered to customers to be unstable, where smooth access to upload and download data is needed by customers.